The complete genome of equid herpesvirus‑1 (EHV‑1) feld isolates from Argentina reveals an interspecifc recombinant strain - Tau, Rocio Lucia; Marandino, Ana Eugenia; Panzera, Yanina; Alamos, Florencia; Vissani, Maria Aldana; Romera, Sonia Alejandra; Perez, Ruben; Maidana, Silvina Soledad (Springer, 2024)
The Equid alphaherpesvirus type 1 (EHV-1) infection can have devastating economic consequences in the horse industry due to large-scale outbreaks of abortions, perinatal foal mortality, and myeloencephalopathy. The present study analyzed the genome of two isolates obtained from aborted fetuses in Argentina, E/745/99 and E/1297/07. The E745/99 genome shares 98.2% sequence identity with Ab4, a reference EHV-1 strain. The E/1297/07 genome shares 99.8% identity with NY03, a recombinant strain containing part of ORF64 and part of the intergenic region from Equid alphaherpesvirus-4 (EHV-4). The E/1297/07 genome has the same breakpoints as other United States and Japanese recombinants, including NY03. The recombinant regions have varying numbers of tandem repeat sequences and different minor parental sequences (EHV-4), suggesting distinct origins of the recombinant events. These are the first complete genomes of EHV-1 from Argentina and South America available in the Databases.